Das Temeswarer Banat Eine europäische Regionalgeschichte - Neumann, Victor (De Gruyter, 2023)
As a region, the Banat has many unique features owing to its specific geographical location, its multi- and intercultural composition, and the cultural diversity of the people who live there. The goal of this volume is to shine a spotlight on the inhabitants of the Banat, to reflect upon their historical experiences, to describe their mentalities, and to show how their attitudes have changed over time.